History of the German-language ENT journals - Stasche, Norbert; Bärmann, Michael (HNO, 2021)
In 1864, the worldwide oldest journal in an area of the later established specialty of otorhinolaryngology was founded as the German Archiv für Ohrenheilkunde (“Archive of Otology”) by its ﬁrst editors Anton von Tröltsch (Würzburg), Adam Politzer (Vienna), and Hermann Schwartze (Halle/S.). Ear, nose, and throat (ENT) topics had previously been published in universal medical journals. In the next few decades, numerous journals in the ﬁeld of ENT were founded, the eventful history of which is presented up to the present day. Particular attention is paid to the historical and personal context of the editors of newly founded magazines and their publishers. The journal landscape, which was changing through acquisitions and mergers of publishers, is described in detail. The merging of the specialties of otology and laryngo-rhinology in Germany, which lasted until the 1920s, had a profound inﬂuence on journal titles and contents. An attempt is made to present the most important titles in their historical development. All the important editors of the German ENT journals are mentioned, although it was not possible to include the names of the editors of the current journals, which are becoming more and more numerous. One chapter deals exclusively with the development of journal publishers. The inserted tables and ﬁgures will help to resolve some of the confusion caused by repeated similar names of journals by showing their historical development.